Developing Skills for Economic Transformation and Social Harmony in China : A Study of Yunnan Province - Liang, Xiaoyan; Chen, Shuang (Washington, DC: World Bank, 2013)
It starts with a demand-side analysis in chapter two, examining historical trends in demand for skills, revealing the types of skills in demand, and projecting future demand for skills driven by economic growth and policy development. Chapter two also highlights the emerging skills shortages and mismatches in Yunnan. The rest of the report focuses on the access, quality, and relevance of Yunnan's education and training system and how effective it is in supplying the skills in demand. An overview of Yunnan's formal and non-formal education and training system is presented in chapter three. Chapter four focuses on the formal Technical and Vocational Education and Training (TVET) system, examining its governance, industry participation, curriculum reforms, quality assurance, and finances. Analysis of the formal education and training system focuses mainly on secondary and tertiary TVET. Chapters five and six address two major training programs outside the formal education system: non-formal training for rural workers and work-based training for urban workers, both of strategic importance. Finally, chapter seven draws on lessons from the Shanghai Program for International Student Assessment, or PISA to demonstrate the role of schools in developing the cognitive skills of 15-year-olds. The report concludes with a summary of findings and a set of policy recommendations for meeting the skills challenges and improving the education and training system.